Unraveling the differential structural stability and dynamics features of T7 endolysin partially folded conformations - Sharma, Meenakshi; Kumar, Dinesh; Poluri, Krishna Mohan (Biochimica et biophysica acta, 2018)
Characterization of partially collapsed protein conformations at atomic level is a daunting task due to their inherent flexibility and conformational heterogeneity. T7 bacteriophage endolysin (T7L) is a single-domain amidase that facilitates the lysis of Gram-negative bacteria. T7L exhibits a pH-dependent structural transition from native state to partially folded (PF) conformation. In the pH range 5–3, T7L PF states display differential ANS binding characteristics. CD, fluorescence, NMR spectroscopy and lysis assays were used to investigate the structure-stability- dynamics relationships of T7L PF conformations. Structural studies indicated a partial loss of secondary/tertiary structures compared to its native state. The loss in the tertiary structure and the hydrophobic core opening increases upon decrease of pH from 5 to 3. Thermal denaturation experiments delineated that the pH 5 conformation is thermally irreversible in contrast to pH 3, depicting that hydrophobic core opening is essential for thermal reversibility. Further, urea dependent unfolding features of PF state at pH 5 and 4 evidenced for a collapsed conformation at intermediate urea concentrations. Residue level studies revealed that α1-helix and β3-β4 segment of T7L are the major contributors for such a structural collapse and inherent dynamics. The results suggested that the low pH PF states of T7L are heterogeneous and exhibits differential structural, unfolding, thermal reversibility, and dynamic features. Unraveling the structure-stability characteristics of different endolysin conformations is essential for designing novel chimeric and engineered phage endolysins as broadband antimicrobial agents over a varied pH range. [Display omitted] •T7L forms partially folded (PF) conformation below pH 6.•Low pH (5, 4, 3) PF forms of T7L have differential structural stabilities.•pH 3 PF state is thermally stable in contrast to pH 4 and 5 PF states.•pH 5 and 4 PF states access molten globule intermediates upon unfolding.•Helix-1 and β3-β4 segment contributes to their structural heterogeneity.